Büchner in Canada: Woyzeck and the Development of English-Canadian Theatre - Wasserman, Jerry (Theatre Research in Canada / Recherches théâtrales au Canada, 1987)
The production history of Büchner’s Woyzeck in Canada’s English-language theatres corresponds closely with the development of an indigenous English Canadian drama during the period of 1960-80. Particular qualities of the style, structure, and political tone of Woyzeck made it an attractive vehicle for the ’alternate’ theatre companies that blossomed during this era. Its most profound impact was felt via the productions of George Luscombe, John Herbert, Richard Rose and Gordon McCall, all of whom were subsequently to do important work which would be indebted to their experience with Büchner’s play. L’histoire des diverses créations de Woyzeck, pièce de Georg Büchner, au Canada anglais correspond de près au développement d’une dramaturgie canadienne-anglaise indigène au cours de la période 1960-1980. Certaines parlicularités de son style, de sa structure, de ses résonances politiques en firent un véhicule tout désigné pour les compagnies théâtrales ’alternatives’ qui foisonnaient à cette époque. Les plus profonds effets de l’oeuvre se firent sentir à travers les productions de George Luscombe, John Herbert, Richard Rose et Gordon McCall qui, influencés tous par la pièce de Büchner, allaient contribuer de façon significative à l’évolution d’un théâtre canadien.